2009
DOI: 10.1016/j.paid.2009.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Increasing emotional intelligence: (How) is it possible?

Abstract: a b s t r a c tThe construct of emotional intelligence (EI) refers to the individual differences in the perception, processing, regulation, and utilization of emotional information. As these differences have been shown to have a significant impact on important life outcomes (e.g., mental and physical health, work performance and social relationships), this study investigated, using a controlled experimental design, whether it is possible to increase EI. Participants of the experimental group received a brief e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
334
4
46

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(407 citation statements)
references
References 29 publications
23
334
4
46
Order By: Relevance
“…These findings support other studies that have examined the contributions of EI training programs and courses in higher education to business people's level of work performance, to levels of emotion identification and emotion management abilities of health professionals (Fletcher, Leadbetter, Curran, & O'Sullivan, 2009;Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009). They are also consistent with Jaeger's (2003) findings, and suggest that EI can be improved in higher education settings, highlighting the need to explore specific teaching strategies for this purpose (Low & Nelson, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…These findings support other studies that have examined the contributions of EI training programs and courses in higher education to business people's level of work performance, to levels of emotion identification and emotion management abilities of health professionals (Fletcher, Leadbetter, Curran, & O'Sullivan, 2009;Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009). They are also consistent with Jaeger's (2003) findings, and suggest that EI can be improved in higher education settings, highlighting the need to explore specific teaching strategies for this purpose (Low & Nelson, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Such interventions increase the likelihood of students developing adaptive coping strategies, seeking support, and being able to stay calm under pressure, which may lead to better adjustment and academic success. The benefits for Running Head: Trajectories of first year university adjustment in the UK 18 university adjustment and academic achievement of using an EI intervention in HE have been demonstrated elsewhere (Dacre-Pool & Qualter, 2012b;Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009;Qualter et al, 2009). …”
Section: Implications Of Findingsmentioning
confidence: 90%
“…Emotional intelligence has been the ability to predict the different variables in empirical research by contributing to further research on emotional intelligence. Some researchers (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011;Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009;Nelis, Kotsou, Quoidbach, Hansenne, Weytens, Dupuis, & Mikolajczak, 2011;Saadi, Honarmand, Najarian, Ahadi, & Askari, 2012;Schutte, Malouff, & Thorsteinsson, 2013) have examined the effectiveness of teaching emotional intelligence and have confirmed their results which state emotional intelligence training has improved emotional intelligence significantly. In this regard, various training programs have been developed to foster emotional and social intelligence based on bar-on theory and it has been demonstrated that emotional and social intelligence have had a significant increase after participating in training program and Bar-on model components can be taught and learned (Freedman, 2003;Orme, 2003).…”
Section: Introductionmentioning
confidence: 96%